Clinical Characteristics of Anti-N-Methyl-d-Aspartate Receptor Encephalitis Overlapping with Demyelinating Diseases: A Review - Zhang, Shujiang; Yang, Yuan; Liu, Wenyu; Li, Zuoxiao; Li, Jinmei; Zhou, Dong (Frontiers in Immunology, 2022)
Anti-N-methyl-d-aspartate receptor encephalitis (NMDARe), a common autoimmune encephalitis, can be accompanied by demyelinating disorders, including multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). To compare the clinical characteristics of patients with different overlapping syndromes, we searched the PubMed database and performed a systematic review. Of the 79 patients with overlapping syndromes, 15 had MS, 18 had aquaporin-4-antibody-positive NMOSD (AQP4-Ab-positive NMOSD), and 46 had MOGAD. Compared with classical NMDARe, overlapping syndromes showed atypical symptoms, such as limb weakness, sensory disturbance, and visual impairments in addition to the main symptoms of NMDARe and a lower ratio of ovarian teratoma. Patients with MOGAD overlap were the youngest, while patients with MS and AQP4-Ab-positive NMOSD overlap tended to be older than patients with classical NMDARe. A majority of patients with NMDARe who overlapped with MS or AQP4-Ab-positive NMOSD were female, but this was not the case for patients overlapped with MOGAD. When NMDARe and demyelinating diseases occurred sequentially, the interval was the longest in patients with NMDARe overlapped with MS. A favorable outcome was observed in patients overlapping with MOGAD, but no robust comparison can be drawn with the patients overlapping with AQP4-Ab-positive NMOSD and MS regarding the small number of available data. The long-term prognosis of overlapping syndromes needs further investigation.